Kenaikan Jabatan Fungsional Pustakawan di Lingkungan Dinas Perpustakaan dan Arsip Daerah Provinsi Jambi - Khairunnisak, Khairunnisak; Mislan, Mislan; Syamsuddin, Syamsuddin (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT Introduction. This study aims to determine the functional promotion in supporting the career of librarians in the Jambi Provincial Archives and Archives Office. The purpose of this study was to determine the process of librarian functional promotion, and supporting and inhibiting factors in the process of librarian functional promotion in supporting the career of a librarian in the Jambi Provincial Library and Archive Service. Data Collection Method. This research uses descriptive qualitative method with a purposive sampling approach. Results and Discussions. From the results of data analysis, it can be found that in the promotion of librarians' functional positions in the Regional Library and Archives Service in Jambi Province, one of them is collecting credit points, and elements for wearing positions by developing careers through education and training, library management, library services, development librarian system, professional development, and there is also a way to attend seminars that include library themes, and similar meetings in the library field. The factors supporting the promotion of the position of librarian in the Jambi Provincial Library and Archives Service are, from the MEMPAN decree and the leadership policy. In the inhibiting factor faced by librarians in the Jambi Provincial Library and Archives Service, namely internal factors originating from the librarians themselves, (librarians) and external factors from outside the librarians themselves (bureaucracy). Conclusion. Libraries in the Jambi Province Regional Library and Archives Service in the librarian promotion have not run optimally. Librarians are expected to work creatively and professionally. Libraries should also carry out more activities and trainings. The librarian position assessment team should carry out and function optimally.